EFFECT OF THE PRESENCE OF CLAY AND LIMESTONE DUST PARTICLES ON THE PHYSICO-MECHANICAL CHARACTERISTIS OF CONCRETE - Zitouni, Salim; Naceri, Abdelghani; Maza, MEKKI (Université de M'sila, 2018)
The effects of clay and limestone dusts in the aggregates on the physico - mechanical characteristics of concrete were investigated. The fine aggregates (dune sand) and coarse aggregates (crushed gravels) used in this study were washed, dried and sieved.Two different mineralogical compositions of dusts (clay and stone) were incorporated in different rates(0%, 5%, 10%, 15%, 20%, 25% and 30%) by replacementin weight of fine (dune sand) and coarse (crushed gravel) aggregates. The presence of clay and limestone dust particles in the fine and coarse aggregates in excessive quantities influenced the physico – mechanical properties of fresh and hardened concrete. The results obtained showed that the effect of clay dust content is more important compared to limestone dust content on the properties of concrete.
Keywords: clay dust, limestone dust, physico-mechanical properties, concrete.